Guinea-Bissau Trade: A Panel Data Analysis - Cateia, Julio Vicente (Asian Development Policy Review, 2019)
Guinea-Bissau became independent in 1973 and since then governments have elaborated different development policies to promote the country's comparative advantages. In the mid-1990s, they promoted the liberalization of the economy and actually the country belongs to several regional economic blocs and it increased its insertion into new extra-continental markets. The purpose of this study is to analyze the determinants of Guinea-Bissau’s exports for the 5 trading partners in the period 1990-2014, using static and panel data dynamic models based on the traditional specification and extended gravity equation of international trade. The static panel data methods suggest that exports react positively to the currency depreciation, incomes, population growth, common language, colonial heritage and geographical proximity (border effects), but decrease with the increase of trade cost, which is consistent with the conventional trade literature. The Arellano and Bond (1991) dynamic panel data model confirms this pattern, also showing a positive correlation between exports and household consumption and investment. These results are important in guiding the country's international trade policies as they suggest the importance of the variables that recur in this standard trade literature.